The Effect of Self-Compassion Therapy on Students’ Learning Self-Efficacy - Gabriel Manek; Nuno da Conçeição Dos Santos (International Journal of Counseling and Psychotherapy, 2025)
Background: Self-efficacy plays a vital role in students’ academic success, yet many learners struggle with low confidence when facing academic challenges. One psychological factor believed to influence self-efficacy is self-compassion, which enables students to respond positively to failure and academic pressure. Objective: This study aims to examine the effect of self-compassion on self-efficacy among students at Ensino Básico Central Lontale. Method: This study employed a quantitative approach with an ex post facto design. The population consisted of 115 students, and a sample of 54 students was selected using a proportional stratified random sampling technique. Data were collected using a self-compassion scale and a self-efficacy scale that were tested for validity and reliability, with Cronbach’s alpha values of 0.758 and 0.623, respectively, indicating acceptable internal consistency. Data were analyzed using descriptive statistics and simple linear regression. Result: The results showed that both self-compassion (M = 42.91, SD = 5.67) and self-efficacy (M = 55.01, SD = 5.15) fell within the medium category. Further analysis revealed that self-compassion had a positive and significant effect on self-efficacy, accounting for 55.9% of the variance (R² = 0.559, p < 0.05). Conlusion: Self-compassion is an important predictor of students’ self-efficacy in learning. Contribution: These findings contribute to educational psychology by highlighting the role of emotional regulation in enhancing academic confidence and suggesting the importance of integrating self-compassion-based interventions in school counseling programs.